The Effects of Virtual Reality Application on Pain Intensity, Anxiety Level and Patient Satisfaction in Patients Who Undergo Bronchoscopy: A Randomized Controlled Trial of article (vol 26, pg 102, 2025) - Sariköse, Aysegül; Turan, Gülcan Bahcecioglu (Elsevier Science Inc, 2026)
[Abstract Not Available]